Peran Guru Dalam Implementasi Pembelajaran Berbasis Data dari hasil AKMI - M. Arifky Pratama; Emy Herawati; Dedi Irama; Yetri Pitriani; Iin Permatasari (UIN Fatmawati Sukarno Bengkulu, 2023)
This study aims to examine the role of teachers at MIN 2 Bengkulu Selatan in implementing data-driven learning based on the results of the 2023 AKMI assessment. Using a qualitative descriptive approach, the research explores how teachers utilize AKMI data to enhance students' literacy and numeracy skills through observation, interviews, and documentation. The findings reveal that teachers play a crucial role in managing data-driven learning, aligning with the theories of Assessment for Learning and Data-Driven Decision Making. AKMI data allows teachers to deeply understand students' strengths and weaknesses, enabling timely interventions. However, challenges such as limited teacher understanding of data analysis and inadequate technological infrastructure persist. Enhancing data literacy and providing technology training are essential to optimizing the use of AKMI data in the learning process. By strengthening these skills, teachers can create more adaptive and responsive learning environments that cater to students' individual needs, significantly improving classroom learning effectiveness.